2015
DOI: 10.1590/0103-8478cr20150079
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and experimental poisoning of cattle by Palicourea aeneofusca in the region of Pernambuco and induction of conditioned food aversion

Abstract: The objective of this study was to describe the epidemiological, clinical, and pathological aspects of Palicourea aeneofusca poisoning in cattle in the region of Pernambuco, Brazil and to determine if it is possible to induce food aversion by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
6
0
2
Order By: Relevance
“…The aforementioned authors concluded that aversion to P. aeneofusca began five days after treatment commencement and persisted for up to 90 days (Oliveira et al 2014). Brito et al (2016) tested the technique of conditioned food aversion to P. aeneofusca in cattle. To this end, animals were divided into two groups of six: one group was composed of animals treated with LiCl at a dose of 175mg/kg shortly after consumption of P. aeneofusca leaves and the other group comprised animals that received 1mL/kg of water, following the same methodology used for the other group.…”
Section: Use Of Conditioned Food Aversion To Prevent Ingestion Of Mfa-containing Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned authors concluded that aversion to P. aeneofusca began five days after treatment commencement and persisted for up to 90 days (Oliveira et al 2014). Brito et al (2016) tested the technique of conditioned food aversion to P. aeneofusca in cattle. To this end, animals were divided into two groups of six: one group was composed of animals treated with LiCl at a dose of 175mg/kg shortly after consumption of P. aeneofusca leaves and the other group comprised animals that received 1mL/kg of water, following the same methodology used for the other group.…”
Section: Use Of Conditioned Food Aversion To Prevent Ingestion Of Mfa-containing Plantsmentioning
confidence: 99%
“…Among the plants that cause sudden death and contain MFA, the most important and responsible for outbreaks of ruminant poisoning in Brazil are P. marcgravii, found in practically all Brazilian territory, except for the southern, semi-arid and northeastern states, and Mato Grosso do Sul state (Tokarnia et al 2012); P. aeneofusca, which is present in the states of Paraíba, Pernambuco, Alagoas and Bahia (Brito et al 2016); A. septentrionalis, formerly Mascagnia rigida (Davis & Anderson 2010), found mainly in the caatinga, on rocky outcrops, in the states of Pernambuco, Alagoas, Rio Grande do Norte, Paraiba and Ceará. A. septentrionalis is in the plants.…”
Section: Introductionmentioning
confidence: 99%
“…Na intoxicação por P. aeneofusca descreveramse lesões inespecíficas no coração, tais como áreas difusas de hemorragia, edema das células de fibras de Purkinje e necrose coagulativa de fibras miocárdicas, com fibras em cariólise ou picnose, aumento da eosinofilia citoplasmática e perda das estriações transversais. Nos miocardiócitos podem ser observados vacúolos intranucleares discretos com marginalização da cromatina e nos espaços intersticiais pode haver edema discreto, depósitos de fibrina e infiltração de células mononucleares (Brito et al 2016, Arruda et al 2017. Possivelmente essas lesões também podem ser encontradas em outras intoxicações por plantas que contêm MFA.…”
Section: Sinais Clínicos Lesões Macro E Microscópicas Associadas àS unclassified
“…Em bovinos foi induzida experimentalmente aversão alimentar condicionada em condições de campo, administrando-se cloreto de lítio após a ingestão de P. aeneofusca. Nessa espécie, o efeito aversivo perdurou por 12 meses, mostrando-se um método eficaz (Brito et al 2016). Em ovinos (Pacífico da Silva & Soto-Blanco 2010) e caprinos (Barbosa et al 2008) a mesma técnica foi utilizada para prevenir a intoxicação por A. septentrionalis com resultados satisfatórios em condições experimentais.…”
Section: Diagnóstico Tratamento E Medidas Preventivas Ou De Controleunclassified
“…The control and prophylaxis of this poisoning by traditional methods such as fencing infested areas or using herbicides is not efficient (Barbosa et al 2003). Therefore, some studies have already used several alternatives to render ruminants resistant to plant poisoning containing MFA, including: 1) the repeated administration of non-toxic doses of the plant containing MFA for alternate periods (Duarte et al 2014); 2) the transfer of ruminal fluid from ruminants inoculated with MFA-degrading bacteria, which became resistant to poisoning, to susceptible ruminants (Silva et al 2015); 3) the administration of MFA-degrading bacteria isolated from the rumen of animals, soil and plants containing MFA (Pessoa et al 2015, Silva et al 2016; 4) use of the conditioned aversion technique through the use of lithium chloride (Brito et al 2016).…”
Section: Introductionmentioning
confidence: 99%